Комбінаторна оптимізація систем нейромережевого криптографічного захисту даних - Різник, В. В.; Riznyk, V. V. (Видавництво Львівської політехніки, 2022)
Розглядається проблема підвищення надійності криптографічного захисту даних в нейромережевих системах з гнучким налаштуванням для забезпечення можливості шифрування (дешифрування) та пересилання повідомлень за допомогою використання сучасних методів комбінаторної оптимізації. В основу комбінаторної оптимізації покладено принцип оптимальних структурних відношень, суть якого полягає в досягненні максимальної різноманітності системи за встановлених обмежень на число структурних елементів і їх взаємного розміщення в просторі-часі. Запропоновано використати для нейромережевого захисту даних сигнально-кодові послідовності, які характеризуються високою завадостійкістю і низьким рівнем функції автокореляції. Здійснено порівняльний аналіз запропонованих послідовностей з класичними кодами. Встановлено взаємозв'язок між інформаційними параметрами оптимізованих сигнально-кодових послідовностей, за яких мінімізується значення функції автокореляції таких послідовностей та досягається їх максимальна коректувальна спроможність. Для криптографічного шифрування (дешифрування) даних запропоновано використати кодові послідовності, в яких кількість різнойменних бінарних символів відрізняються між собою не більше, ніж на один символ, що дає змогу мінімізувати значення функції автокореляції кодованого сигналу при фіксованій розрядності кодових послідовностей. Окреслено можливість формування шифрування (дешифрування) повідомлень шляхом використання різного виду оптимізованих сигнально-кодових послідовностей залежно від поставлених вимог до функціонування системи нейромережевого криптографічного захисту даних за конкретних умов забезпечення необхідної надійності охорони зашифрованих повідомлень з урахуванням обмежень на тривалість надсилання та рівня шумів в каналах зв'язку.

The problem of improving the reliability of cryptographic data protection in neural network systems with flexible configuration is considered. To ensure the possibility of encrypting/decrypting messages it is proposed to use combinatorial optimization methods for the tasks of forming encoded sequences with improved quality indicators for correcting ability, noise immunity, and autocorrelation properties. The basis of combinatorial optimization is the principle of optimal structural relationships, the essence of which is to achieve the maximum diversity of the system under the established restrictions on the number of structural elements and their mutual placement in space-time. It is proposed to use signal-code sequences for neural network data protection, which are characterized by high noise immunity and low level of the autocorrelation function, using various types of optimized code sequences depending on the set of requirements for work under specific conditions, taking intoaccount restrictions on the duration of sending encrypted messages and the presence of noise in communication channels. The system for neural network cryptographic data protection has been developed using encoded signal sequences, where the number of binary characters of different names differs by no more than one character, which minimizes the value of the autocorrelation function of the encoded signal at a fixed bitdepth. To ensure high technical and economic indicators of the cryptosystem, it is advisable to equip it with specialized modules of neuro-similar elements of the network with the possibility of training and flexible configuration for cryptographic data encryption. The relationship between the parameters of optimized encoded signal sequences, in which the value of the autocorrelation function is minimized, and the maximum achievable number of detected and corrected errors has been established. It is proposed to use unique properties of combinatorial configurations with a non-uniform distribution of structural elements, which are distinguished by the fact that the set of all ring sums of their numerical values occurs a fixed number of times. A comparative analysis of cryptographic methods for data protection and transfer using non-standard codes built on the so-called IRB code sequences together with other signal-code constructions was carried out.
Combinatorial optimization of systems of neural network cryptographic data protection
Keywords: принцип оптимальних структурних відношень; ідеальна кільцева в'язанка; кодова ІКВ-послідовність; кодова послідовність Баркера; функція автокореляції; principle of optimal structural relationships; ideal ring bundle (IRB); IRB code sequence; Barker code sequence; autocorrelation function